Forms of Existential Crisis in Haruki Murakami’s Norwegian Wood: Toru Watanabe Analysis - Prameswari, Dyah Ayu; Marsih, Linusia (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2023)
This study will focus on Toru Watanabe's forms of existential crisis reflected in Haruki Murakami's Norwegian Wood (1987). To analyze the existential crisis experienced by Toru Watanabe, Jean-Paul Sartre's theory of existentialism is applied. Furthermore, Butėnaitė-Świtkiewicz’s theory of components of existential crisis is also used to describe the components of existential crisis, namely emotional, cognitive, and behavioral components. This study applies the descriptive qualitative method. In addition, philosophical and psychological approaches are employed in this study due to the fact that this study is concerned with the existentialism in philosophy and existential crisis in psychology. The results of the study show that Toru Watanabe suffers from an existential crisis because of his inability to seek meaning for his existence. His existential crisis is indicated through the emotional, cognitive, and behavioral components.